2008
DOI: 10.1093/applin/amm022
|View full text |Cite
|
Sign up to set email alerts
|

Formulaic Sequences: Are They Processed More Quickly than Nonformulaic Language by Native and Nonnative Speakers?

Abstract: It is generally accepted that formulaic sequences like take the bull by the horns serve an important function in discourse and are widespread in language. It is also generally believed that these sequences are processed more efficiently because single memorized units, even though they are composed of a sequence of individual words, can be processed more quickly and easily than the same sequences of words which are generated creatively (Pawley and Syder 1983). We investigated the hypothesized processing advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
296
1
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 492 publications
(329 citation statements)
references
References 46 publications
24
296
1
8
Order By: Relevance
“…That is, there is a positive association between frequency of occurrence in language (speech and/or text), familiarity and processing ease. While this link had been previously established for individual words (Gernsbacher 1984;Oppenheimer 2006), it seems to apply to word combinations as well, with collocations generally being high in frequency of use, familiarity, and ease of processing (Conklin and Schmitt 2008;Durrant 2008).…”
Section: The Familiarity Hypothesismentioning
confidence: 86%
See 1 more Smart Citation
“…That is, there is a positive association between frequency of occurrence in language (speech and/or text), familiarity and processing ease. While this link had been previously established for individual words (Gernsbacher 1984;Oppenheimer 2006), it seems to apply to word combinations as well, with collocations generally being high in frequency of use, familiarity, and ease of processing (Conklin and Schmitt 2008;Durrant 2008).…”
Section: The Familiarity Hypothesismentioning
confidence: 86%
“…are not only used more frequently, but are also processed more quickly by language users (Conklin and Schmitt 2008). That is, there is a positive association between frequency of occurrence in language (speech and/or text), familiarity and processing ease.…”
Section: The Familiarity Hypothesismentioning
confidence: 99%
“…Third, formulaic language has processing advantages. There is now ample evidence to show that formulaic sequences are processed faster and more accurately than creatively generated language (Conklin and Schmitt, 2008). Fourth, formulaic language can improve the overall impression of L2 learners' language production.…”
Section: Spoken Fluency C2mentioning
confidence: 99%
“…Pawley and Syder (1983) claim that formulaic sequences, even though they consist of a sequence of individual words, can be processed more easily and quickly than single memorized units. By comparing the reading times for formulaic forms and non-formulaic ones for both native and nonnative speakers, Conklin and Schmitt (2006) found that the former forms were read more quickly by both groups of participants.…”
Section: Literature Review and Theoretical Groundsmentioning
confidence: 99%